Validation of A Critical Thinking Test in Mathematics for Senior High School - Ma. Rachel Kim L. Aure; Enriqueta D. Reston (JME (Journal of Mathematics Education), 2020)
Critical thinking equips a person with the competencies needed and develops the power of the mind extensively. The development of critical thinking is known as an essential goal in educational systems. However, the assessment of critical thinking is not an easy feat. This study validated the critical thinking skills test in mathematics for senior high school students based on a model of critical thinking skills and learning areas of the K to 12 Mathematics Curriculum. The instrument validation process to 902 respondents through cluster sampling from different senior high schools. With an initial 45 items on three dimensions of critical thinking, the test's final form consisted of only 30 items after the items were screened based on the validation process. The content validation was carried out through an expert examination of the items and a comparison of the test results developed with Cornell's critical thinking for criterion-related validity evidence (r = 0.299, p < 0.01). Construct validation by factor analysis, and results generated 13 factors accounting for 58.51% of the variance. These results indicated that the developed mathematics critical thinking test measured other than the specified critical thinking skills model used. The developed test may try to assess students' critical thinking in the context of mathematics. Furthermore, this may contribute to promoting teaching and assessment strategies gears towards the development of students' mathematical critical thinking.